Enhancing human capital through holistic education approach: a Malaysian perspective - Ismail, Maymunah; Ahmad, Nor Halawah; Abdul Rasool, Mohamed Saladin (2023)
Knowledge and confidence equipped with values such as innovative, disciplined, enthusiastic, patriotic, tenacious and competitive are important characteristics of human capital. Improving the quality of human capital in a country will enhance the development of a holistic society towards achieving a high-income nation status. In addition, it is capable to realize sustainable economic growth in the long run. The present paper discusses the importance of education as an agent of change to produce quality human capital and increase their marketability. The paper deliberates on various issues and challenges faced in developing a quality education framework towards producing a holistic human capital that matches job market requirements of a high income nation status. Specifically, the paper provides a comprehensive guidelines in producing an innovative human capital in the digital era.